Quarkus in action - Štefanko, Martin; Martiška, Jan (Manning Publications, 2025)
Quarkus in Action provides a carefully designed learning path through Quarkus' key features and use cases. You'll learn hands-on by implementing a working car rental application with a cloud-native microservices design that includes Kubernetes, SQL and NoSQL databases, messaging, and observability. Along the way, you'll learn how Quarkus simplifies deployment on cloud platforms like OpenShift.
Online resource; title from title details screen (O'Reilly, viewed April 9, 2025)
Keywords: Application software -- Development -- Computer programs; Application program interfaces (Computer software); Open source software; Java (Computer program language); Web services; Cloud computing; Logiciels d'application; Développement; Logiciels; Interfaces de programmation d'applications; Logiciels libres; Java (Langage de programmation); Services Web; APIs (interfaces); Audiobooks; Livres audio